IDENTIFIKASI GEJALA PERUBAHAN IKLIM DI KOTA BANDAR LAMPUNG BERDASARKAN DATA IKLIM MAKRO TAHUN 1998-2020: Studi Kasus : Kota Bandar Lampung - Pratiwi, Fennidya Nur; Asbi, Adnin Musadri; Kurnianingsih, Nela Agustin (LPPM Universitas Terbuka, 2022)
Climate change today is an important thing that can affect people's lives and development in thefuture. For this reason, each stakeholder needs to prepare a strategic program in dealing with thephenomenon of climate change in order to reduce the impact it will cause. In this case of the program, it is important for stakeholders to know how the climate conditions in the area they cover. This study aims to identify the symptoms of climate change that occur in Bandar Lampung City based on two indicators, namely: Pattern of Changes in Air Temperature; Rainfall Change Pattern; and historical events related to climate change. This research was conducted using a qualitative approach with multiple linear regression method and a qualitative approach with a descriptive narrative method. The results of this study indicate that the city of Bandar Lampung in the last ± 23 years has experienced symptoms of climate change in the form of changes in rainfall patterns and air temperature as wellas the impacts of climate change such as the phenomenon of tidal flooding.